The effects of gender on problem solving skills of nursing students in Turkey: a meta-analysis study Türkiye’deki hemşirelik öğrencilerinin problem çözme düzeylerine cinsiyetin etkisi: Bir meta analiz çalışması - Kantek, Filiz; Yeşilbaş, Hande (Journal of Human Sciences, 2019)
The aim of this study is to the effects of gender on problem solving skills of nursing student using meta-analysis method in Turkey. Online databases were scanned to reach studies to be included in the survey. In scanning ’problem solving’, ’student nurse’, ’Turkey’, ’problem solving skill’ keywords were used in Turkish and English. Six studies that meet the criteria were included in the study. The CMA statistical program was used in the analysis of the data. Q and I2 values to test heterogeneity and, Orwin’s Fail-Safe N and Tau coefficients to publication bias of the included studies were calculated. A random effects model was used to examine the effect size. The six studies’ total sample size was 2079 nursing students, 436 male and 1643 female. Heterogeneity and publication bias test showed that studies were heterogeneous and there was not publication bias. The mean effect size on gender problem solving was calculated as 0.079. In conclusion, it was identified that the effect of gender on problem solving level of student nurses was insignificant for women. For future studies, it will be useful to conduct meta-analysis studies on the different factors that affect the problem solving level of student nurses. Extended English summary is in the end of Full Text PDF (TURKISH) file. Özet Bu çalışmanın amacı, meta analiz yöntemi kullanarak Türkiye’deki hemşirelik öğrencilerinin problem çözme beceri düzeylerine cinsiyetin etkisini belirlemektir. Online very tabanları kullanılarak araştırmaya dahil edilecek çalışmalara ulaşıldı. Taramada ‘problem çözme-problem solving’, ‘öğrenci hemşire- student nurse’’, ‘Türkiye-Turkey’, ‘problem çözme becerisi- problem-solving skill’ anahtar kelimeleri kullanıldı. Dahil edilme kriterlerine uygun olan altı çalışma araştırmaya dahil edildi. CMA istatistik programını kullanarak veri analizi sağlandı. Meta analize dahil edilen çalışmaların heterojenliğini ve yayın yanlılığını test etmek için Q ve I2 değerleri, Orwin’s Fail-Safe N ve Tau katsayısı hesaplandı. Etki büyüklüğünün incelenmesinde rastgele etkiler modeli kullanıldı. Araştırmaya dahil edilen altı çalışmanın toplam örneklem büyüklüğü 2079 hemşirelik öğrencisi olup, 436’sı erkek ve 1643’ü kadındı. Heterojenlik ve yayın yanlılığı testi çalışmaların heterojen olduğunu ve yayın yanlılığının olmadığını gösterdi. Cinsiyetin problem çözme üzerine ortalama etki büyüklüğü 0.079 olarak hesaplandı. Sonuç olarak öğrenci hemşirelerin problem çözme düzeyine cinsiyetin etkisinin kadınlar lehine önemsiz düzeyde olduğu belirlendi. Gelecek çalışmalar için öğrenci hemşirelerin problem çözme düzeyini etkileyen farklı faktörlere ilişkin meta analiz çalışmalarının yapılması yararlı olacaktır.